ʺCharacteristics of augmented reality technology and its application in the educational process of higher education establishmentsʺ. - Wang, Bo (Problems of Engineer-Pedagogical Education, 2024)
The use of augmented reality technology in the educational process of higher education establishments affects its productivity, which is determined by the significant potential for personality development both in social relations and in various spheres of creative self-realization. The article examines the definition of «augmented reality» by modern scientists. The tools of augmented reality technology are defined as a set of hardware and software computer support for supplementing the real world surrounding a person with context-dependent virtual objects in a specific space and time, which changes when the real environment or observation angle changes. The main components of the technology are augmented reality hardware, augmented reality browser, recognition system, augmented reality system, augmented reality content. There are different classifications of augmented reality technology. According to the type of interaction of the augmented reality system with the user, autonomous and interactive augmented reality systems are distinguished. According to the degree of mobility, stationary and mobile augmented reality systems are distinguished. According to their functional purpose, visual search and recognition systems, Augmented Reality 2.0 systems, lens/screen-mirror systems, and contextual visualization systems are distinguished. Also described are the features of the application of augmented reality technology as a means of learning in a higher education establishment, which contributes to increasing the visibility and informative of the educational process when studying various disciplines. Increasing the effectiveness of the educational process involves a more detailed study of the feasibility and ways of using augmented reality technology based on available literary sources and conducted research, which will make it possible to determine the possibilities of using this technology as an object of study and a means of learning.